Exploring the link between parents’ differentiation of self and children’s externalizing behavior problems: the mediating role of need-supportive vs. need-frustrating parenting practices - Klein, Michal; Levy, Tomer; Shulman, Cory; Lwow, Etan; Silberg, Tamar (Frontiers in Psychology, 2024)
Objective: Externalizing behavior problems (EBPs) are common in children, with significant long-term impact on the child and family members. Parents, particularly mothers, of children with EBPs often experience heightened emotional distress. One crucial factor affecting parents' ability to manage this distress is their level of differentiation-of-self (DOS). Differentiated parents are more likely to engage in practices that meet their child’s psychological needs, thus supporting the self-determination theory principles vital for a child’s well-being. This study examined the impact of parental DOS on parenting practices and subsequently on the child's EBPs, exploring possible differences between mothers and fathers. Methods: Thirty-two mother-father dyads with children aged 6-14, diagnosed with EBPs participated. Parents completed the Differentiation of Self Inventory–Short Form, the Revised Parents as a Social Context Questionnaire, and the Strengths and Difficulties Questionnaire to assess parental DOS, practices, and child’s EBPs, respectively. Adjusted parallel mediation models examined the mediating role of parental practices in the relationship between parental DOS and a child’s EBPs. Results: While no direct link between parental DOS and child’s symptoms was found, a complete mediation model indicated need-frustrating practices mediating between parental DOS and a child’s EBPs, for both mothers and fathers. Additionally, fathers' need-supportive practices, but not mothers', were negatively associated with the child’s symptoms. Discussion: These findings highlight the interaction between parental traits, need-frustrating practices, and a child’s psychopathology. Notably, fathers' supportive behaviors emerged as potential protective factors against child’s EBPs, suggesting promising directions for future research and interventions targeting fathers.